Epigenetic Memory in Mammals - Migicovsky, Zoe; Kovalchuk, Igor (Frontiers in Genetics, 2011)
Epigenetic information can be passed on from one generation to another via DNA methylation, histone modifications and changes in small RNAs, a process called epigenetic memory. During a mammal’s lifecycle epigenetic reprogramming, or the resetting of most epigenetic marks, occurs twice. The first instance of reprogramming occurs in primordial germ cells and the second occurs following fertilization. These processes may be both passive and active. In order for epigenetic inheritance to occur the epigenetic modifications must be able to escape reprogramming. There are several examples supporting this non-Mendelian mechanism of inheritance including the prepacking of early developmental genes in histones instead of protamines in sperm, genomic imprinting via methylation marks, the retention of CenH3 in mammalian sperm and the inheritance of piwi-associated interfering RNAs. The ability of mammals to pass on epigenetic information to their progeny provides clear evidence that inheritance is not restricted to DNA sequence and epigenetics plays a key role in producing viable offspring.